The Effect of Personality, Education, Training, and Competence on the Performance of BPKP Representatives in East Java Province - Wicaksono, Mochamad Imam Arif; Purwanto, Purwanto; Rahayu, Sri (Neo Journal of economy and social humanities, 2026)
Employee performance in government internal audit institutions is essential for ensuring accountability, transparency, and effective public financial supervision. However, empirical studies often examine psychological factors and human capital components separately, resulting in limited understanding of how these internal resources jointly influence employee performance. This study aims to analyze the effects of personality, education, training, and competence on employee performance at the Regional Representative Office of the Financial and Development Supervisory Agency (BPKP) in East Java Province. This research employed a quantitative explanatory approach using a census method involving 141 employees. Data were collected through structured questionnaires and analyzed using multiple linear regression with SPSS. The results indicate that personality, education, training, and competence all have positive and significant effects on employee performance. Among these variables, competence emerged as the most dominant predictor (β = 0.392; p < 0.001). The regression model also demonstrates strong explanatory power with an Adjusted R² value of 0.731, indicating that 73.1% of the variance in employee performance is explained by the four variables. These findings highlight the importance of integrating psychological characteristics and human capital development in strengthening employee performance within government oversight institutions.